Management Tasks and Theoretical Basis (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
this article covers the concept, content and essence of management. In addition, management tasks and theoretical foundations are explained in detail. The description of management in economic, social, spiritual-educational, psychological fields is mentioned. Management subject and object, as well as management methods are explained. Henri Fayol's management principles are explained.